Strategi Perencanaan Paket Wisata Gwk Sebagai Main Destination - Nugraha, Rizki Nurul; Khaeriyah, Khaeriyah; Wulan, Wulan (Peneliti.net, 2023)
Travel is done to relax yourself after the saturation of daily activities. To make it easier for tourists who want to take a vacation without the headache of taking care of everything, they can use the services of travel agents who have prepared tour packages according to their goals. Therefore, this research discusses